2013
DOI: 10.1007/s13139-013-0197-5
|View full text |Cite
|
Sign up to set email alerts
|

Differential Diagnosis of Borderline Ovarian Tumors from Stage I Malignant Ovarian Tumors using FDG PET/CT

Abstract: Purpose Borderline ovarian tumors (BOTs) are more common in young women of reproductive age, and exhibit a better prognosis than malignant ovarian tumors (MOTs). Fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT) were compared in their ability to differentiate BOTs from stage I MOTs. Methods Among 173 patients who had preoperative FDG PET/CT due to ovarian neoplasms between November 2006 and March 2009, there were 13 patients with BOTs or stage I MOTs. For differential diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…Although the expression of GLUT1 was increased in CSCs compared to non-CSCs in jHOC5, the concomitant decrease in LAT1 expression could still indicate that glutamine accumulation was important in the CSCs of jHOC5. Recent studies have demonstrated that the high expression levels of LAT1 and the high uptake of glucose were correlated with poor prognosis in ovarian (clear cell) carcinoma (4,(22)(23)(24). These facts may reflect the status in which CSCs differentiate and propagate into non-CSC, indicated by our in vitro data.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Although the expression of GLUT1 was increased in CSCs compared to non-CSCs in jHOC5, the concomitant decrease in LAT1 expression could still indicate that glutamine accumulation was important in the CSCs of jHOC5. Recent studies have demonstrated that the high expression levels of LAT1 and the high uptake of glucose were correlated with poor prognosis in ovarian (clear cell) carcinoma (4,(22)(23)(24). These facts may reflect the status in which CSCs differentiate and propagate into non-CSC, indicated by our in vitro data.…”
Section: Discussionsupporting
confidence: 66%
“…One technique in clinical practice that takes advantage of glycolysis is fluorodeoxyglucose positron emission tomography/computed tomography (FDG-PET/CT) (2,3). Normally, in cancer cells, glucose is transported into the cytoplasm via glucose transporters (GLUTs), especially GLUT1 (4). Unlike glucose, FDG is a glucose-like substance that is also transported into tissues but is not further metabolized, resulting in its accumulation in tissues with active glucose metabolism (5).…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al retrospectively reviewed imaging on 13 early FIGO StageI malignant ovarian tumours or borderline tumours and found that SUVmax was significantly lower in the group with borderline tumours. 8 The SUVmax of the borderline tumours was significantly lower than malignant lesions (2.9 ± 1.5 vs 6.6 ± 2.9); however,no significant difference was seen in age at presentation, CA-125, tumour size, or metabolic tumour volume. SUVmax of 3.7 was the best threshold value to differentiate between borderline and malignant tumours with a sensitivity of 83.3% and specificity of 85.7%.…”
Section: Role Of 18 F-fdg Pet Ct In Ovarian Cancermentioning
confidence: 73%
“…Positron emission tomography integrated with computed tomography (PET/CT) using 18 F-fluorodeoxyglucose (FDG) is widely used in clinical oncology. 9,10 FDG is an analog of glucose, and increased tumor FDG uptake reflects enhanced glycolytic activity of tumor cells, which is a universal manifestation of altered metabolism of transformed cells. 11,12 Not only malignant diseases, but also benign inflammatory diseases have been successfully evaluated by FDG-PET/CT with high sensitivity, owing to the fact that enhanced glycolytic activity is a hallmark of activated inflammatory cells.…”
Section: Introductionmentioning
confidence: 99%